The metacommunication: an approach to their qualities for the taking of decisions of the industrial engineer - Ríos Barrios, Isabel (2021)
The work has the purpose of basing the qualities metacognitive, semiotics and pragmatic of the communication for the taking of decisions. It is shown the lacks that this sense maintains some focuses related with the communication. The treated aspects constitute an approach to the metacommunication from the conceptual foundations that intend, their structure and components. Finally, it is noticed the necessity and importance of the thematic one in the industrial engineer’s formation through the analysis of the influence that exercises in them the opportune behavior in the interactive process that you/they facilitate a bigger effectiveness in the managerial strategy and as consequence bigger contribution to the competitiveness in the company